Clinical characteristics and risk factors of relative systemic hypertension and hypertension among sickle cell patients in Cameroon - Nguweneza, Arthemon; Ngo Bitoungui, Valentina Josiane; Mnika, Khuthala; Mazandu, Gaston; Nembaware, Victoria; Kengne, Andre P.; Wonkam, Ambroise (Frontiers in Medicine, 2022)
Increased blood pressure (BP) has been associated with higher risk of stroke and mortality in Sickle Cell Disease (SCD). We investigated risk factors associated with Relative Systemic Hypertension (RSH) or systemic hypertension in SCD patients in Cameroon. Using R, Multivariate multinomial logistic regression modelling was used to examine the effects of the demographic, anthropometric, clinical, and laboratory factors to determine risk factors. A total of 815 individuals with SCD, including 380 (46.6%) males were analysed. At baseline, the median age [interquartile range] was 18.0 [12.0–25.0] years, ranging from 3 to 66 years. Approximately three-quarters of the patients (n = 645; 79.1%) had normal BP, 151 (18.5%) had RSH and 19 (2.3%) had hypertension. Age (P <.001) and gender (P = 0.022) were significantly different across the BP categories. Weight (P <.001), height (P <.001), BMI (P <.001), pulse pressure (P= 0.020), history of stroke (P= 0.012), haemoglobin level (P = 0.002), red blood cell count (P = 0.031), creatinine (P <.001), and (estimated glomerular filtration rate) eGFR (P = 0.002) was also significantly different across the three BP categories. After adjustment, the significantly associated factors of RSH in the SCD patients were age [OR = 1.03, 95% CI = 1.01-1.06), p <.010], male gender [OR = 1.54, 95% CI = 1.04- 2.27), P=0.029], BMI [OR = 1.10, 95% CI = 1.04-1.17), P=0.001]. After adjustment, the independent variables significantly associated factors of Hypertension in the SCD patients were age [OR = 1.05, 95% CI = 1.01–1.10), p = 0.034], male gender [OR = 3.31, 95% CI = 1.04–10.52), p = 0.042], BMI [OR = 1.14, 95% CI = 1.01-1.29), p = 0.027]. Creatinine was significantly associated with RSH [OR =1.31(1.05-1.63, p = 0.016]. SCD patients with RSH or hypertension maybe at increased risk of renal dysfunction. We found the relatively high prevalence of RSH and hypertension (20.8%) in SCD patients in Cameroon. Tailored Interventions that consider major risk factors (age, gender, and BMI) may lower BP pressure and prevent severe complications.